Effects of probiotics on patients with Prader–Willi syndrome: a systematic review and meta-analysis of randomized controlled trials - Toh, Qin-Ying; Kang, Yi-No; Chee, Siew-Yin; Chiu, Hsin-Hui (Frontiers in Nutrition, 2025)
BackgroundPrader-Willi Syndrome (PWS) involves growth, obesity, and behavioral challenges; probiotics may improve symptoms through the gut-brain axis, aiding treatment. This meta-analysis aimed to assess the impact of probiotic supplementation on individuals with PWS in terms of probiotic abundance, psycho-social outcomes, behavioral issues, and adverse events.MethodsWe systematically conducted searches across PubMed, the Cochrane Central Register of Controlled Trials, EMBASE, and the Web of Science. Our study included relevant randomized controlled trials (RCTs) published before February 2025. Two independent review authors evaluated study eligibility, extracted data, and assessed the risk of bias in the included studies. Data synthesis employed a random-effects model based on heterogeneity test results and was presented as the standardized mean difference (SMD) with a 95% confidence interval (CI).ResultsA total of five RCTs were included. Probiotic supplementation led to a notable increase in the abundance of the Bifidobacterium genus (SMD 1.21; 95% CI, 0.02 to 2.39). Notably, 12 weeks of probiotics intake demonstrated a favorable trend on social engagement (SMD −0.68; 95% CI: −1.14 to −0.21; p = 0.004). In contrast, probiotics did not exhibit a significant influence on behavioural problems, and the safety of probiotics consumption was assured as there was no significant increase in gastrointestinal adverse events.ConclusionThe validation of a probiotic treatment for PWS is currently an aspirational goal. Additional investigation is required to comprehensively comprehend the connection between PWS and the gut microbiome, as well as its potential ramifications for the disease phenotype.Systematic review registrationPROSPERO, CRD42023416791.